ANALISIS PERBEDAAN ABNORMAL RETURN SEBELUM DAN SESUDAH PENGUMUMAN COVID-19 SEBAGAI PANDEMI GLOBAL OLEH WHO (Studi pada Pasar Modal Negara-Negara ASEAN) - Muti'ah, Annisaul; Anwar, Muhadjir (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Event study is a research methodology used to analyze market reactions andresponses to certain events. This research uses the object of research in the capitalmarkets of ASEAN countries. The purpose of this research is to analyze thedifference in abnormal returns between before and after the announcement ofCOVID - 19 as a global pandemic by WHO. The population used is the capitalmarket of ASEAN countries using the purposive sampling method as a samplingtechnique and the analysis using the paired samples t-test test for 39 days ofobservation period consisting of 10 days of estimation period and 29 days of eventperiod (14 days before the event). 1 day event date, 14 days after the event). Theresults of this research stated that descriptively there was an abnormal returnbetween before and after the WHO event officially declared COVID-19 as a globalpandemic, then using the paired samples t-test test proved that there was nodifference in abnormal returns before and after the WHO event which officiallydeclared COVID -19 as a global pandemic.